1974
DOI: 10.1139/f74-207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Accumulation of Methylmercuric Chloride and p,p′DDT by Rainbow Trout (Salmo gairdneri)

Abstract: Amounts of mercury and DDT residues accumulated from water by yearling rainbow trout (Salmo gairdneri) in the laboratory increased as water temperature increased. Fish exposed to methylmercuric chloride at concentrations of 234–263 parts per trillion for 12 wk at 5, 10, and 15 C accumulated 1.19, 1.71, and 1.96 ppm; fish exposed to p,p′DDT at concentrations of 133–176 parts per trillion accumulated 3.76, 5.93, and 6.82 ppm. Concentrations of mercury accumulated by the fish were significantly different (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Investigators have also estimated the types of waterborne (e.g., 30-250 parts per trillion) Hg exposure scenarios 164 L. I. SWEET AND J. T. ZELIKOFF Weiner and Nylander (1996) Fish consumption 12-200 µg/d Eisenmann and Miller (1996); Chan et al (1999) Total diet study, 0.004-0.078 mg/d Ysart et al (1999) various countries b that can result in bioaccumulated residues in fish tissue that exceed health guidelines (Reinert et al, 1974;McKim et al, 1976).…”
Section: Sources Of Exposurementioning
confidence: 99%
“…Investigators have also estimated the types of waterborne (e.g., 30-250 parts per trillion) Hg exposure scenarios 164 L. I. SWEET AND J. T. ZELIKOFF Weiner and Nylander (1996) Fish consumption 12-200 µg/d Eisenmann and Miller (1996); Chan et al (1999) Total diet study, 0.004-0.078 mg/d Ysart et al (1999) various countries b that can result in bioaccumulated residues in fish tissue that exceed health guidelines (Reinert et al, 1974;McKim et al, 1976).…”
Section: Sources Of Exposurementioning
confidence: 99%
“…Similarly localized pollutants can then take a toll disproportionate to their effects should both pollutants and fish be dispersed throughout the baydelta system. Fish aggregated in zones of preferred temperatures are often performing physiologically at high rates, a condition that can accelerate bioaccumulation and toxicity of pollutants (Reinert et al 1974). Dissolved oxygen can be depleted in zones of cool water needed by fish.…”
Section: Temperature Preferencementioning
confidence: 99%
“…Black et al [6] showed that temperature change had a proportional effect on the uptake of oxygen and the three toxicants, benzo[ a ]pyrene, tetrachlorobiphenyl, and naphthalene, by fish gills. Accumulation of DDT by rainbow trout was increased by 45% between 5 and 15°C [43]. Accumulation of DDT by mosquito fish ( Gambusia holbrooki ) was three times greater at 20°C than at 5°C [44].…”
Section: Discussionmentioning
confidence: 99%